Novel erectile analyses revealed augmentable penile Lyve‐1, the lymphatic marker, expression - Kota Fujimoto; Daiki Hashimoto; Sang Woon Kim; Yong Seung Lee; Takuya Suzuki; Masanori Nakata; Shinji Kumegawa; Shinichi Asamura; Gen Yamada (Reproductive Medicine and Biology)
Abstract Purpose The pathophysiology of penis extends to erectile dysfunction (ED) to conditions including sexually transmitted diseases (STDs) and cancer. To date, there has been little research evaluating vascular drainage from the penis. We aimed to evaluate penile blood flow in vivo and analyze its possible relationship with the lymphatic maker. Materials and Methods We established an in vivo system designed to assess the dynamic blood outflow from the corpus cavernosum (CC) by dye injection. To analyze lymphatic characteristics in the CC, the expression of Lyve‐1, the key lymphatic endothelium marker, was examined by the in vitro system and lipopolysaccharide (LPS) injection to mimic the inflammatory conditions. Results A novel cavernography methods enable high‐resolution morphological and functional blood drainage analysis. The expression of Lyve‐1 was detected along the sinusoids. Furthermore, its prominent expression was also observed after penile LPS injection and in the erectile condition. Conclusions The current in vivo system will potentially contribute to the assessment of penile pathology from a novel viewpoint. In addition, current analyses revealed inducible Lyve‐1 expression for LPS injection and the erection state, which requires further analyses on penile lymphatic system.